2015
DOI: 10.1159/000371494
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Vitrectomy and Chorioretinectomy in Perforating Eye Injuries

Abstract: Purpose: To evaluate the anatomical and functional results of patients who underwent pars plana vitrectomy for perforating eye injuries as well as to analyze the benefit of the chorioretinectomy procedure. Methods: Retrospective and descriptive study of 24 eyes of 22 patients with perforating eye injuries operated on at the Centro Hospitalar do Porto between January 2006 and December 2012. Results: An early vitrectomy was accomplished in 67% of the eyes and a delayed vitrectomy in 33% of the eyes. A concomitan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…As in previously published studies concerning PCR (Ozdek et al, 2013, Ferreira et al, 2015, the rate of PVR development was low in our series, seen in 16% of the injured eyes (as opposed to the expected >60% reported in the literature) and requiring multiple reoperations. However, in no eye did the PVR originate from the treatment (PCR) site, but from elsewhere in the vitreous cavity.…”
Section: Yessupporting
confidence: 73%
See 1 more Smart Citation
“…As in previously published studies concerning PCR (Ozdek et al, 2013, Ferreira et al, 2015, the rate of PVR development was low in our series, seen in 16% of the injured eyes (as opposed to the expected >60% reported in the literature) and requiring multiple reoperations. However, in no eye did the PVR originate from the treatment (PCR) site, but from elsewhere in the vitreous cavity.…”
Section: Yessupporting
confidence: 73%
“…Ozdek et al (2013) and Ferreira et al (2015) have confirmed the benefit of this proactive surgical technique performed during the "acute" (the primary surgery) or "subacute" (within the first 100 hr) stage; in this article we present our own results from early PCR to prevent PVR in the severely injured eye.…”
Section: Introductionmentioning
confidence: 66%
“…As vitreous hemorrhage, vitreous and inflammatory component incarceration are frequent and known factors in PVR development, an early vitrectomy allows their immediate removal, which has at least the theoretical advantage of minimizing PVR development. Ferreira et al [10], Schrader [29], Coleman [30], and De Juan et al [31] reported better visual outcome in eyes that underwent early vitrectomy. The results of our study contribute to confirming this tendency: 15 out of 27 eyes (55.6%) that underwent early vitrectomy regained a visual acuity of 40/200 or better versus 1 out of 4 eyes (25%) that underwent delayed vitrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Ozdek et al [9], the PVR rate was 2 out of 13 patients (15.3%) when the procedure could be accomplished. In 2015, Ferreira et al [10] reported a PVR rate of only 7% in the subgroup of patients with a perforating globe injury that underwent a prophylactic chorioretinectomy. Within this study, only 4 out of 31 eyes with a complete chorioretinectomy developed PVR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation